Rapid curing material for repairing ground of coal mine tunnel and use method of rapid curing material

By using a fast curing material composed of base materials, initiators and catalysts on the ground of coal mine tunnels, the problems of slow curing speed and high brittleness of existing materials in high humidity environments are solved, and the rapid and effective repair of underground ground is achieved. , and improves transportation efficiency and corrosion resistance.

CN119409892APending Publication Date: 2025-02-11INNER MONGOLIA HUANGTAOLEGAI COAL CO LTD SHI LIN CHEM BRANCH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411474251.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

The existing coal mine tunnel ground repair materials have slow curing speed in high humidity environments, and have problems such as high brittleness and heat-proneness, which cannot meet the needs of efficient and rapid downhole repair.

Method used

A fast curing material is used, which includes a base material, an initiator and a catalyst. The base material consists of monohydric alcohol acrylate, polyhydric alcohol acrylate, acrylic resin, heavy calcium carbonate and hard mineral powder. The initiator is methyl ethyl ketone peroxide or benzoyl peroxide, and the catalyst is cobalt cycloalkane or methylaniline . The material can be repaired quickly by stirring and standing.

Benefits of technology

The material can cure quickly in a high humidity downhole environment, reaching a compressive strength of 45-55MPa within 30 minutes, reducing construction time, improving downhole transportation efficiency, and having good corrosion resistance and leakage resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005095589970000021
    Figure BDA0005095589970000021
Patent Text Reader

Abstract

The invention discloses a rapid curing material for repairing the ground of a coal mine tunnel and a use method thereof, and belongs to the field of high-performance materials. The rapid curing material comprises the following components: base materials: acrylic monohydric alcohol ester and acrylic polyol ester are added into a reaction kettle and stirred for 10 minutes, acrylic resin powder is gradually added, after 10 minutes, stirring is continued for 20 minutes, after acrylic resin is completely dissolved, ground calcium carbonate is added into the reaction kettle, stirring is continued for 20 minutes, hard mineral powder is added, and after stirring is continued for 20 minutes, the base materials are uniformly mixed; stirring for 20 minutes to obtain a base material; the initiator is methyl ethyl ketone peroxide or benzoyl peroxide; the catalyst is cobalt naphthenate or methylaniline. The curing speed of the curing material is high, the compressive strength of 45-55 MPA can be achieved within 30 minutes, the pavement repairing time can be shortened, rapid traffic opening is achieved, and the underground transportation efficiency is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a fast-curing material for repairing coal mine tunnel ground and a use method thereof, belonging to the field of high-performance materials. Technical Background

[0002] The air humidity in coal mines is relatively high, and they are in a hot and humid environment for a long time. At the same time, there are a large number of heavy-loaded transport vehicles and shovel loaders passing through. The harsh environment and heavy pressure conditions can easily cause rutting, cracking, deformation and other damages to the transport road surface. In severe cases, the road surface may sink, misalign, and break. In order to ensure the production and transportation efficiency and safe production of the mine, it is urgent to repair the transport road surface quickly in a short time. Conventional underground road repairs usually use conventional curing silicate cement or ordinary curing organic polymers, but due to the slow curing speed, transportation operations usually have to be stopped during construction, which seriously affects the progress of the work. At present, the main method for rapid repair of underground non-track road damage in China is to use quick-drying aluminum silicate cement composite mortar or organic polymer fast-curing materials for repair. These materials have been used underground in specific mining areas.

[0003] However, both quick-drying aluminum silicate cement composite mortar and organic high molecular polymer fast-curing materials have defects during use. Aluminum silicate cement composite mortar has a fast curing speed, and its strength can reach more than 20MPa within 1 hour, but the formed cured material is very brittle and cannot withstand the long-term crushing of heavy-loaded transport vehicles underground. Pure organic high molecular polymers cannot be used on a large scale because of the heat generation phenomenon, which poses a dangerous hidden danger to the flammable and explosive environment of the mine with a lot of gas. How to achieve fast and effective curing of damaged ground paving without obvious heat release under high humidity conditions underground is the main way to solve the problem of rapid repair and opening of underground roads and improve the efficiency of underground mineral mining.

[0004] Therefore, the current road repair materials should be condensed and hardened or solidified as soon as possible, with high early strength to ensure the construction progress and realize the rapid opening of the road; in addition, the repair materials should also have excellent durability, including impermeability, corrosion resistance, wear resistance and high strength, etc., so that they can still meet the long-term use requirements even in a high-pressure, high-humidity and heavy-load environment; the repair materials must also meet the requirements of being green, non-toxic and environmentally friendly; finally, while ensuring the excellent performance of the repair materials, the materials should also be cheap and easy to construct. Based on the above, the present invention has developed a rapid road repair material, which is green, environmentally friendly, non-toxic and sustainable, while being reasonably priced, with simple construction technology and low energy consumption. After the underground road construction, it can support the travel of large and heavy-loaded vehicles for a long time, and can withstand the damage of the humid environment underground, improve the efficiency of underground construction operations, and ensure safe underground operations and production.

[0005] CN101260638A discloses a method for rapid hardening of mudstone in the bottom plate of a mine tunnel, wherein the mudstone is directly hardened in the tunnel, and a hardened roadbed is obtained by vibrating and rolling the mudstone with a roller, and a surface layer is laid on the hardened roadbed. After the surface layer is maintained, a complete roadbed pavement is formed; a curing agent is added during the rapid hardening process, and the curing agent is composed of 50-55% sulphoaluminate cement clinker, 30-40% slaked lime, 1.5-2.5% sodium sulfate, 1.5-2.5% sodium silicate, and 2-4% potassium thiochlorate. The method can quickly repair the road surface and reduce the environmental damage caused by the waste mudstone.

[0006] CN115745559A discloses a quick remodeling material for underground coal mine concrete pavement, the formula of which is 14-16 parts of slag, 8-10 parts of water glass, 1-2 parts of sodium hydroxide, 8-10 parts of water, and 90-100 parts of waste concrete; water glass, sodium hydroxide and water-supported activator solution are mixed with slag to form a gel material, and the broken concrete in the tunnel is crushed and mixed with the gel material for paving to complete the tunnel remodeling. This method utilizes broken concrete on site, saves time, has a fast molding time, and has a high pavement hardness.

[0007] Most of the existing technologies use the original concrete slag as raw material, and then add auxiliary materials, and complete the road repair after simple mixing and stirring. However, the road surface repaired by this method is not strong enough and often cracks and breaks again soon, which affects normal production. Summary of the invention

[0008] In order to overcome the defects in the prior art, the present invention discloses a fast curing material for repairing the ground of a coal mine tunnel, wherein the curing material comprises the following components:

[0009] Base material: Add monohydric acrylate and polyhydric acrylate to the reactor, stir for 10 minutes, gradually add acrylic resin powder, continue stirring for 20 minutes after the addition is completed, and after the acrylic resin is completely dissolved, add heavy calcium carbonate to the reactor, continue stirring for 20 minutes, then add hard mineral powder and stir for 20 minutes to obtain the base material.

[0010] Initiator: methyl ethyl ketone peroxide or benzoyl peroxide;

[0011] Catalyst: cobalt naphthenate or methylaniline;

[0012] The mass ratio of base material, initiator and catalyst is 100:0.1-1:0.01-0.05, more preferably 100:0.2-0.5:0.02-0.03.

[0013] The chemical reaction equation involved in the curing reaction process is as follows:

[0014]

[0015] The monoacrylic acid ester and polyacrylic acid ester in the base material will copolymerize to form a highly elastic copolymer. After adding acrylic resin, it will entangle and crosslink with the molecular chain of the resin to form a complex spatial network structure, significantly improving the mechanical properties of the crosslinked product. The reaction equation only expresses the possible polymerization process. The long-chain polymers generated by the copolymerization reaction are entangled with each other to form a complex three-dimensional spatial crosslinked structure, which cannot be accurately expressed by the reaction equation.

[0016] The weight proportions of the components in the base material are 40-60 parts of monohydric alcohol acrylate, 20-30 parts of polyhydric alcohol acrylate, 1-8 parts of acrylic resin, 5-15 parts of heavy calcium carbonate, and 30-60 parts of hard mineral powder; preferably, the weight proportions of the components in the base material are 40-50 parts of monohydric alcohol acrylate, 20-25 parts of polyhydric alcohol acrylate, 2-5 parts of acrylic resin, 5-10 parts of heavy calcium carbonate, and 40-50 parts of hard mineral powder.

[0017] The monohydric alcohol acrylate is one or more of methyl methacrylate, butyl methacrylate, butyl acrylate, methyl acrylate, ethyl methacrylate, ethyl acrylate, and propyl methacrylate; the polyhydric alcohol acrylate is one or more of pentaerythritol triacrylate, pentaerythritol tetraacrylate, glycerol triacrylate, glycerol trimethacrylate, glycerol diacrylate, and glycerol dimethacrylate; and the weight average molecular weight of the acrylic resin is 5000-100000.

[0018] The particle size of the heavy calcium carbonate is 1-100 μm, preferably 20-50 μm; the hard mineral powder is one of coal gangue, iron slag and steel slag, and the particle size of the hard mineral powder is 0.1-10 mm, more preferably 1-5 mm.

[0019] A method for quickly repairing the ground of a coal mine tunnel using the solidified material comprises the following steps:

[0020] (1) Add all components at once according to the base material composition and mix and stir for 5-15 minutes;

[0021] (2) Add initiator and catalyst to the base material, stir for 1-5 minutes, fill into cracks or potholes on the ground, and let it stand for 10-30 minutes to achieve rapid repair of the road surface.

[0022] The ground rapid solidification material can reach a compressive strength of 45-55 MPa after being left standing for 30 minutes.

[0023] The construction process of the method can be carried out at room temperature, that is, the reaction is carried out outdoors, and the reaction temperature varies with the ambient temperature, which is -10°C to 30°C. During the curing construction, the temperature will rise as the curing reaction proceeds, and the temperature generally rises to no more than 50°C, preferably no more than 45°C.

[0024] Beneficial effects of the present invention:

[0025] 1. Rapid road repair adds high heat capacity solid powder, which reduces the sharp temperature rise caused by reaction exotherm during the curing process. The solid powder also contains an appropriate number of hydroxyl active sites, which is conducive to forming chemical bonds with the carboxyl groups in the polymer, improving the cross-linking and dispersion of the material, and further improving the mechanical strength of the material, making it suitable for use in underground environments.

[0026] 2. The viscosity of the quick repair material is low, so there is no need to clean the damaged road surface during construction. Grouting can be carried out directly, which reduces the time for road cleaning and improves the repair efficiency.

[0027] 3. Rapid repair materials cure quickly and can reach a compressive strength of 45-55MPA within 30 minutes, which can reduce the time for road repair, achieve rapid traffic, and improve underground transportation efficiency.

[0028] 4. After curing, the rapid repair pavement material has good corrosion resistance, can withstand the temperature and humidity environment underground, and has obvious anti-leakage effect. DETAILED DESCRIPTION

[0029] Example 1

[0030] The base material consists of 20 parts of methyl methacrylate, 20 parts of butyl acrylate, 10 parts of methyl acrylate, 15 parts of pentaerythritol triacrylate, 12 parts of pentaerythritol tetraacrylate, 3 parts of acrylic resin, 10 parts of heavy calcium carbonate and 50 parts of hard mineral powder; the average particle size of the heavy calcium carbonate is 65 μm; the heavy mineral powder is iron slag with an average particle size of 0.6 mm.

[0031] The initiator is 0.5 parts of methyl ethyl ketone peroxide;

[0032] Catalyst: 0.05 parts of cobalt naphthenate.

[0033] Using the solidified material to quickly repair the ground of a coal mine tunnel includes the following steps:

[0034] (1) Add all components at once according to the base material composition and mix and stir for 15 minutes;

[0035] (2) Add initiator and catalyst to the base material, stir for 3 minutes, fill in a hole with a diameter of 25 cm and a depth of 9 cm, and test the compressive strength of the repaired road surface after standing for 30 minutes to reach 51 MPa. After 3 hours, the compressive strength of the road surface reached 55 MPa. The ambient temperature during the repair process was 18°C, and the highest surface temperature of the curing material during the curing process was 42°C.

[0036] Example 2

[0037] The base material consists of 20 parts of ethyl methacrylate, 20 parts of butyl methacrylate, 10 parts of methyl acrylate, 12 parts of pentaerythritol triacrylate, 15 parts of glycerol triacrylate, 5 parts of acrylic resin, 8 parts of heavy calcium carbonate and 45 parts of hard mineral powder; the average particle size of the heavy calcium carbonate is 65 μm; the heavy mineral powder is steel slag with an average particle size of 1 mm.

[0038] The initiator is 0.5 parts of benzoyl peroxide;

[0039] Catalyst: 0.05 parts of cobalt naphthenate.

[0040] Using the solidified material to quickly repair the ground of a coal mine tunnel includes the following steps:

[0041] (1) Add all components at once according to the base material composition and mix and stir for 15 minutes;

[0042] (2) Add initiator and catalyst to the base material, stir for 3 minutes, fill in a hole with a diameter of 10 cm and a depth of 6 cm, and test the compressive strength of the repaired road surface after standing for 30 minutes to reach 55 MPa. After 3 hours, the compressive strength of the road surface reached 58 MPa. The ambient temperature during the repair process was 15°C, and the highest surface temperature of the curing material during the curing process was 41°C.

[0043] Example 3

[0044] The base material consists of 20 parts of methyl methacrylate, 20 parts of butyl acrylate, 10 parts of butyl methacrylate, 15 parts of glycerol diacrylate, 15 parts of pentaerythritol tetraacrylate, 3 parts of acrylic resin, 10 parts of heavy calcium carbonate and 50 parts of hard mineral powder; the average particle size of the heavy calcium carbonate is 65 μm; the heavy mineral powder is coal gangue with an average particle size of 1 mm.

[0045] The initiator is 0.5 parts of methyl ethyl ketone peroxide;

[0046] The catalyst is 0.05 parts of methylaniline.

[0047] Using the solidified material to quickly repair the ground of a coal mine tunnel includes the following steps:

[0048] (1) Add all components at once according to the base material composition and mix and stir for 15 minutes;

[0049] (2) Add initiator and catalyst to the base material, stir for 3 minutes, fill in a pothole with a diameter of 22 cm and a depth of 12 cm, and test the compressive strength of the repaired road surface after standing for 30 minutes to reach 48 MPa. After 3 hours, the compressive strength of the road surface reached 52 MPa. The ambient temperature during the repair process was 25°C, and the highest surface temperature of the curing material during the curing process was 49°C.

[0050] Example 4

[0051] The base material consists of 20 parts of methyl methacrylate, 18 parts of propyl acrylate, 10 parts of methyl acrylate, 15 parts of pentaerythritol triacrylate, 12 parts of pentaerythritol tetraacrylate, 3 parts of acrylic resin, 10 parts of heavy calcium carbonate and 50 parts of hard mineral powder; the average particle size of the heavy calcium carbonate is 65 μm; the heavy mineral powder is steel slag with an average particle size of 0.8 mm.

[0052] The initiator is 0.8 parts of benzoyl peroxide;

[0053] Catalyst: 0.05 parts of cobalt naphthenate.

[0054] Using the solidified material to quickly repair the ground of a coal mine tunnel includes the following steps:

[0055] (1) Add all components at once according to the base material composition and mix and stir for 15 minutes;

[0056] (2) Add initiator and catalyst to the base material, stir for 3 minutes, fill in a pothole with a diameter of 35 cm and a depth of 10 cm, and test the compressive strength of the repaired road surface after standing for 30 minutes to reach 54 MPa. After 3 hours, the compressive strength of the road surface reached 59 MPa. The ambient temperature during the repair process was 23°C, and the highest surface temperature of the curing material during the curing process was 48°C.

[0057] Example 5

[0058] The base material consists of: 15 parts of methyl methacrylate, 25 parts of butyl acrylate, 5 parts of methyl acrylate, 10 parts of propyl methacrylate, 15 parts of pentaerythritol triacrylate, 15 parts of pentaerythritol tetraacrylate, 3 parts of acrylic resin, 10 parts of heavy calcium carbonate and 50 parts of hard mineral powder; the average particle size of the heavy calcium carbonate is 65 μm; the heavy mineral powder is iron slag with an average particle size of 0.5 mm.

[0059] The initiator is 0.5 parts of methyl ethyl ketone peroxide;

[0060] The catalyst is 0.05 parts of methylaniline.

[0061] Using the solidified material to quickly repair the ground of a coal mine tunnel includes the following steps:

[0062] (1) Add all components at once according to the base material composition and mix and stir for 15 minutes;

[0063] (2) Add initiator and catalyst to the base material, stir for 3 minutes, fill in a pothole with a diameter of 8 cm and a depth of 3 cm, and test the compressive strength of the repaired road surface after standing for 30 minutes to reach 50 MPa. After 3 hours, the compressive strength of the road surface reached 53 MPa. The ambient temperature during the repair process was 21°C, and the highest surface temperature of the curing material during the curing process was 46°C.

[0064] Comparative Example 1

[0065] No heavy mineral powder and heavy calcium carbonate are added to the base material composition, and the rest is the same as in Example 1.

[0066] After 30 minutes of standing, the compressive strength of the repaired road surface reached 32MPa, and after 3 hours, the compressive strength of the road surface reached 36MPa. The ambient temperature during the repair process was 18°C, and the highest surface temperature of the curing material during the curing process was 55°C.

[0067] Comparative Example 2

[0068] No heavy mineral powder is added to the base material composition, and the rest is the same as in Example 1.

[0069] After 30 minutes of standing, the compressive strength of the repaired road surface reached 39MPa, and after 3 hours, the compressive strength of the road surface reached 41MPa. The ambient temperature during the repair process was 18°C, and the highest surface temperature of the curing material during the curing process was 58°C.

[0070] Comparative Example 3

[0071] No heavy calcium carbonate was added to the base material composition, and the rest was the same as in Example 1.

[0072] After 30 minutes of standing, the compressive strength of the repaired road surface reached 34MPa, and after 3 hours, the compressive strength of the road surface reached 35MPa. The ambient temperature during the repair process was 18°C, and the highest surface temperature of the curing material during the curing process was 54°C.

[0073] Comparative Example 4

[0074] In the base material composition, the monohydric acrylate was replaced by an equal mass fraction of polyhydric acrylate, and the rest was the same as in Example 1.

[0075] After 30 minutes of standing, the compressive strength of the repaired road surface reached 43MPa, and after 3 hours, the compressive strength of the road surface reached 46MPa. The ambient temperature during the repair process was 18°C, and the highest temperature of the curing material surface during the curing process was 47°C.

[0076] Comparative Example 5

[0077] In the base material composition, the acrylic acid polyol ester was replaced by an acrylic acid monool ester in an equal mass fraction, and the rest was the same as in Example 1.

[0078] After 30 minutes of standing, the compressive strength of the repaired road surface reached 45MPa, and after 3 hours, the compressive strength of the road surface reached 46MPa. The ambient temperature during the repair process was 18°C, and the highest surface temperature of the curing material during the curing process was 48°C.

[0079] Comparative Example 6

[0080] The particle size of the heavy mineral powder in the base material composition is 15 mm, and the rest is the same as in Example 1. The ambient temperature during the repair process is 18°C, and the highest surface temperature of the solidified material during the solidification process is 46°C.

[0081] After standing for 30 minutes, the compressive strength of the repaired road surface was tested to be 46MPa. After 3 hours, the compressive strength of the road surface was tested to be 50MPa.

[0082] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent transformations made using the contents of the present invention specification, or directly or indirectly applied in related technical fields, are also included in the patent protection scope of the present invention.

Claims

1. A fast curing material for repairing coal mine tunnel ground, the curing material comprising the following components: Base material: Add monohydric alcohol acrylate and polyhydric alcohol acrylate to the reactor, stir for 10 minutes, gradually add acrylic resin powder, continue to stir for 20 minutes after the addition is completed, and after the acrylic resin is completely dissolved, add heavy calcium carbonate to the reactor, continue to stir for 20 minutes, add hard mineral powder, and stir for 20 minutes to obtain the base material; Initiator: methyl ethyl ketone peroxide or benzoyl peroxide; Catalyst: cobalt naphthenate or methylaniline.

2. The solidifying material according to claim 1, characterized in that: The mass ratio of base material, initiator and catalyst is 100:0.1-1:0.01-0.

05.

3. The solidifying material according to claim 1, characterized in that: The weight proportions of the components in the base material are 40-60 parts of monohydric alcohol acrylate, 20-30 parts of polyhydric alcohol acrylate, 1-8 parts of acrylic resin, 5-15 parts of heavy calcium carbonate and 30-60 parts of hard mineral powder.

4. The solidifying material according to claim 1, characterized in that: The monohydric alcohol acrylate is one or more of methyl methacrylate, butyl methacrylate, butyl acrylate, methyl acrylate, ethyl methacrylate, ethyl acrylate, and propyl methacrylate; the polyhydric alcohol acrylate is one or more of pentaerythritol triacrylate, pentaerythritol tetraacrylate, glycerol triacrylate, glycerol trimethacrylate, glycerol diacrylate, and glycerol dimethacrylate; and the weight average molecular weight of the acrylic resin is 5000-100000.

5. The solidifying material according to claim 1, characterized in that: The particle size of the heavy calcium carbonate is 1-100 μm; the hard mineral powder is one of coal gangue, iron slag and steel slag, and the particle size of the hard mineral powder is 0.1-10 mm.

6. The solidifying material according to claim 5, characterized in that: The particle size of the heavy calcium carbonate is 20-50 μm; the particle size of the hard mineral powder is 1-5 mm.

7. A method for quickly repairing the ground of a coal mine tunnel using the solidified material according to any one of claims 1 to 6, comprising the following steps: (1) Add all components at once according to the base material composition and mix and stir for 5-15 minutes; (2) Add initiator and catalyst to the base material, stir for 1-5 minutes, fill into cracks or potholes on the ground, and let it stand for 10-30 minutes to achieve rapid repair of the road surface.

8. The method according to claim 7, characterized in that: The ground rapid solidification material can reach a compressive strength of 45-55 MPa after being left standing for 10-30 minutes.

9. The method according to claim 7, characterized in that: The construction process of the method can be carried out at room temperature, which is -10°C to 30°C, and the ground temperature rises by no more than 50°C during the construction process.

10. The method according to claim 9, characterized in that: During the construction process, the ground temperature rise shall not exceed 45°C.

Citation Information

Patent Citations

  • Rapid curing method for mine laneway muddy bottom

    CN101260638A